STUDI PARAMETER OSEANOGRAFI FISIKA DAN KIMIA DI PERAIRAN PULAU SULAWESI, INDONESIA - Luhur Moekti Prayogo; Irvan Aris Kurniawan (Universitas Hang Tuah, 2021)
Sulawesi Island is one of Indonesia's largest islands and is known to have potential in the marine sector, both in tourism and fisheries. Sulawesi island is crossed by the equator line in the northern quarter so that most of its territory is in the southern hemisphere. The diverse geography of the island of Sulawesi causes differences in the characteristics of the oceanographic parameters. The salinity and tides of seawater are oceanographic parameters that can affect biota's survival in the waters. This research aims to study the chemical physics oceanography parameters, which include tides and salinity in the waters of the island of Sulawesi using NOAA and BIG data. The research that has been done showed that the waters around the island of Sulawesi had an average high water level of 1.3 meters and a low water level of 0.9 meters. Then from the calculation, the Formzahl number is 0.8 (0,25 < F £ 1,5), which means that the tidal type is in the Mixed category, tends to be semi-diurnal. The salinity analysis results showed that in July 2020, the salinity content ranged from 29.63 to 36.45 ppt, with an average of 33.99 ppt. In November 2020, the salinity content ranged from 25.71 to 39.74 ppt with an average of 33.50 ppt. In February 2021, the salinity content ranged from 27.23 to 37.73 ppt with an average of 33.00 ppt. The lowest salinity was obtained in the rainy season in November 2020, and the highest salinity content was in the same month in a small part of the region. In the dry season, seawater's average salinity content in Sulawesi waters is relatively high compared to the rainy season, with the lowest content value of 29.63 ppt.